Convenient fabrication of a core–shell Sn@TiO2 anode for lithium storage from tinplate electroplating sludge. Issue 70 (4th August 2020) - Lin, Zhihua; Liu, Xueming; Xiong, Xunhui; Wei, Shizhong; Liu, Weizhen; Lin, Zhang
Abstract : A convenient route was developed for the fabrication of a high-performance core–shell Sn@TiO2 anode for LIBs from tinplate electroplating sludge. Abstract : We here report a unique preparation of a high-performance core–shell Sn@TiO2 anode for lithium ion batteries (LIBs) from tinplate electroplating sludge via a convenient process without deep purification. The Sn@TiO2 shows excellent electrochemical performance due to its core–shell structure. This work provides insight into addressing the electroplating sludge and designing high-performance LIB anodes.